Steps to operationalize a rewilding decision: Focus on functional types - du Toit, Johan T. (Frontiers in Ecology and Evolution, 2023)
If transparent and inclusive stakeholder discussion delivers a consensus for active rewilding, then five steps are recommended for operationalizing that decision, focused initially on the large herbivore assemblage. First, determine the potential biomass density (kg/km2) of large mammalian herbivores in the target landscape. Regression models based on rainfall or primary productivity are helpful if applicable, otherwise comparative studies are needed. Second, use empirical data from reference ecosystems to apportion biomass density among functional types, crudely defined by body size and feeding type (grazer, browser, mixed feeder). Third, identify specific functional traits (coarse grazing, endozoochory, etc.) of particular local importance. Fourth, identify species within each functional type that are already present, estimate their potential biomass densities, and thus identify the shortfall within each cell of the body size x feeding type matrix. A candidate set of native and non-native (surrogate) species is then identified to make up the shortfalls. This is followed by an iterative process of estimating equilibrium population sizes, stakeholder acceptance, viability of each potential population, and options for periodic augmentations of chronically small populations. Fifth, stakeholders must be inclusively re-engaged to visualize the potential assemblage, its expected functional interactions, the ecosystem services to be delivered, and the long-term costs (including opportunity costs) and benefits. When a plan is supported, local stakeholders should be integrated as active participants in the implementation, monitoring, and championing of their rewilding project.